ADVENTURES IN MARXIST THEORY toward a reconstruction of marxism in the contemporary era. - KELLNER, DOUGLAS (ROUTLEDGE, 2025)
Adventures in Marxist Theory provides an introduction and overview of Marxian theory to demonstrate its contemporary relevance to social and political theory and a range of disciplines from philosophy to economics in both the humanities and the social sciences. The text argues that current historical developments and the evolution of economics, politics, society, culture, technology, and everyday life demonstrates the contemporary relevance of Marxism in both theory and politics in the contemporary era.The book presents a twenty-first century Marxism relevant to theorizing contemporary state capitalist and technological societies, critically dissecting their major social and political issues and problems, while advancing progressive social transformation in the interests of increased democracy and social justice. The volume opens with an Introduction describing a multi-disciplinary and critical approach to Marxism and its application to a wide range of contemporary issues, including the alienation of labor in the workplace, social divisions, and injustices such as classism, sexism, racism, and homophobia, and questions of technology, social media, and AI, as well as problems of ecological crisis, autocracy, and state oppression. Specific chapters address the Marxian critique of capitalism and theory of socialism, its concept of ideology and morality, its methodological synthesis of social science, critical theory, and its analyses of globalization, technology, and democracy.Written by a distinguished scholar of Marxism, critical theory, and cultural and political studies, the volume will be a key resource for instructors, students, and readers in historical and contemporary sociology, social and critical theory, political sociology, political and cultural studies, and Marx and Marxist studies.
Keywords: Marx, Karl, -- 1818-1883.; Communism.; Socialism.; elektronické knihy; electronic books